Differences in the Effect of Recovery Time in Distributed Practice on Accuracy of Bolavoli Bump Service Assessed from Blood Muscular Power on the Bolavoli Intermediate Putra Athlete - Roudhotul Janah; Sugiyanto Sugiyanto; Slamet Riyadi (BIRCU, 2021)
Various studies were conducted to try to improve the accuracy in performing the volleyball jump service, either by simple exercises to modification of the form of training. The purpose of this study was to determine the difference in the effect of recovery time in distributed practice and leg muscle power on the accuracy of volleyball jump service. This research was conducted on volleyball athletes at Vita Surakarta club. The research method used is an experimental method with a 2x2 factorial design, the sample size in this study was 40 athletes obtained through total sampling technique. Data analysis techniques in this study used ANOVA, Saphiro-Wilk test (Lilliefors test with α = 0.05) and variance homogeneity test (Leve's test with α = 0.05). The results showed that (1) athletes who were given training using long recovery times had a significant effect on the accuracy of the volleyball jump service compared to athletes who were given training using short recovery times. (2) athletes who have high leg muscle power have a significant effect on the accuracy of the volleyball jump service compared to athletes who have low leg muscle power. (3) there is an interaction between the recovery time and leg muscle power on the accuracy of the volleyball jump service.